Q. 124.3( 40 Votes )

# If y = cos^{–1} x, Find d^{2}y/dx^{2} in terms of y alone.

Answer :

It is given that y = cos^{–1} x

Now,

Therefore,

………………………(1)

Now it is given that y = cos^{–1} x

⇒ x= cosy

Now putting the value of x in equation (1), we get

Rate this question :

If y = A e ^{– kt} cos (pt + c), prove that , where n^{2} = p^{2} + k^{2}.

If y = (sin^{–1} x)^{2}, prove that: (1–x^{2}) y_{2} – xy_{1}– 2=0

If log y = tan^{–1} X, show that : (1+x^{2})y_{2}+(2x–1) y_{1}=0.

If y = a {x + √x^{2} + 1}^{n} + b{x – √x^{2} + 1} ^{– n}, prove that (x^{2} – 1) .

If y = 3 cos (log x) + 4 sin (log x), prove that: x^{2}y_{2}+xy_{1}+ y =0.

If y =e^{tan–1x}, Prove that: (1+x^{2})y_{2}+(2x–1)y_{1}=0

If , y = a sin t, evaluate at

RD Sharma - Volume 1If x = a (1 + cos θ), y = a (θ+ sinθ) Prove that .

RD Sharma - Volume 1If, prove that .

RD Sharma - Volume 1If x = a (θ – sin θ), y = a (1 + cos θ) find .

RD Sharma - Volume 1